(untitled) (Baghdad Science Journal, 2011)
The possible effect of the crude aqueous extract of soy bean seeds on some blood parameters (total count of red blood cells, white blood cell , (total and differential) blood platelates, packed cell volume and concentration of blood hemoglobin) was studied in 20 albino female mice which were allocated in four experimental groups (5 mice/group). The first group was orally treated with distilled water (control group) while the second, third and fourth group were given a concentration of 4%, 6% and 8% of the extract, respectively. At the end of the daily gavaging, which lasted for 4 weeks, the animals were killed, after recording their life body weight, and blood samples were collected from each mice to study the effect of the extract on the above mentioned parameters. Some of the active ingredients in the soy bean seeds extract were analytically tested. This test showed that the extract contained flavonoids and saponins. The effect of the extract on the studied blood parameters is reflected by the following results: 1) Significant (P